PENGARUH MASA KERJA, PELATIHAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BANK SULSELBAR CABANG UTAMA MAKASSAR - Andi Nur Karima; Idayanti Nursyamsi; Fauziah Umar (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Quality human resources is one of the strengths owned by a company to achieve goals, one of which is to improve employee productivity. This study aims to analyze the extent to which influence factors work, training, and motivation to optimize work productivity achieved by employees at PT. Bank Sulselbar Main Branch of Makassar. The research method used is descriptive, validity, and multiple linear regression analysis using SPSS softaware. From the calculation results obtained t value for the variable Working Period is equal to 10,818 and by using the significance level (significance level) of 5% obtained t table of 1.671 while the sig value in the table of 0.000 because sig smaller than 0.05 that shows that Masa Work (X1) has a positive and significant effect on Work Productivity (Y). The value of t arithmetic for the training variable is 2,360 while the sig value in the table is 0,021 so it shows that Training (X1) has a positive and significant influence on Work Productivity (Y). The t value for the Motivation variable is 4,172 and by using the significance level (significance level) of 5% obtained t table equal to 1.671 while the sig value in the table is 0.000 so that the Motivation (X3) has a positive and significant effect to the Work Productivity (Y) . While simultaneously, the calculation results obtained F-count larger than the F-table is 390.687> 2.53 While the sig value in the table of 0.000 is smaller than 0.005 indicates that the variable Working Period (x1), Training (x2), Motivation (X3) effect simultaneously or together to work productivity variable.